FLAW TOLERANT ALUMINA / ZIRCONIA MULTILAYERED COMPOSITES - Hatton, Benjamin (My University, 1998)
Ceramic composites for high temperature applications must be designedwith crack arrest capability to improve the resistance to flaws produced in service, such as by thermal shock. Laminated composites containing A12O3 layers in 3mol%Y2O3-ZrO2 (TZ3Y) were fabricated by electrophoretic deposition (EPD) and pressureless sintering. The layering design (A12O3 layer thickness and volume fraction) was varied to determine the influence on fracture behaviour. The residual stress in A12O3 layers was measured using a fluorescence spectroscopy technique. The fracture strength of 15 different laminates, and monolithic A12O3 and TZ3Y, was tested in 4-point bending at room temperature. Vickers indentation (10 kg load) was used to simulate natural flaws at the sample surface before testing as a measure offlaw tolerance. Fracture ranged from catastrophic failure, to multi-stage failure and complete delamination (in processing). Transitions in behaviour were found related to a geometrical parameter derived from the strain energy release rate for edge cracks. The strength ofthree A12Q3/TZ3Y composites was compared with monolithic A12O3 and TZ3Y for a range ofindentation loads (up to 20 kg). The strength ofthe composites was similar to monolithic TZ3Y but the flaw tolerance was improved due to multi-stage fracture. The strength and flaw tolerance (using 10 kg indentation) oftwo A12O3/TZ3Y composites and monolithic TZ3Y was measured £ 1300°C. The multi-stage fracture behaviour disappeared > 250C, and there was no beneficial effect ofthe A12O3 layers on the strength. Superplastic deformation of the TZ3Y layers at 1300°C was prevented by the constraint of the A12O3 layers. Recommendations are made about the design of flaw tolerant ceramic laminates for high temperature use.